Assessment of Exercise Testing after Repair of Tetralogy of Fallot. (2nd September 2012) - Kotby, A. A.; Elnabawy, H. M.; El-Guindy, W. M.; Abd Elaziz, R. F.
Abstract : Tetralogy of Fallot (TOF) is the most common form of cyanotic congenital heart disease. The aim of this study was to examine the exercise performance of young patients following the repair of TOF and to assess the influence of different variables related to the surgical repair on exercise testing. This study was conducted on 21 patients (16 males and 5 females) operated on for TOF compared to 15 healthy age- and sex-matched control children. The patients' median age at time of the study was 8 years (range 5–13 years) while age at surgical repair was 5 ± 2.1 years (range 2–10 years). Patients were subjected to 2D and color Doppler echocardiographic examination. Treadmill exercise stress testing was performed for all subjects according to modified Bruce protocol. The resting ECGs of all patients revealed normal sinus rhythm and RBBB. Cases had lower exercise capacity when compared to control subjects and those with aortopulmonary shunt showed significantly lower exercise performance when compared to those without aortopulmonary shunt. In conclusions, exercise tolerance after total correction of TOF is slightly impaired on short-term followup with more affection among patients with previous aortopulmonary shunts. The present study did not reveal any serious ventricular arrhythmia.